Seasonal changes of body mass, body composition, and muscular performance in collegiate wrestlers - Buford, T. W.; Smith, D. B.; O'Brien, M. S.; Warren, A. J.; Rossi, S. J. (International Journal of Sports Physiology and Performance, 2008)
Purpose: The purpose of the present investigation was to examine the physiological response of collegiate wrestlers to their competitive season. Methods: Eleven Division I collegiate wrestlers (mean ± SD; 19.45 ± 1.13 y) volunteered and completed 4 testing sessions throughout the course of the collegiate wrestling season. Testing sessions were conducted pre-, mid-, and postseason, as well as before the national tournament. Testing consisted of weigh-in, skinfold body composition testing, and a 50-rep concentric, isokinetic leg extension muscle endurance test (180°/s). Muscular performance variables measured included peak torque, peak torque at fatigue, percent decline, and peak torque/body mass ratio. Results: A significant increase (P < .05) of 2.9% was observed for body mass between midseason and postseason (2.38 kg). From pre- to postseason, a mean increase of 3.8% (3.1 kg) was observed for body mass. An increase (P < .05) in BF% of 2.9% was observed between prenationals and postseason. No significant differences (P > .05) were observed between consecutive time points for quadriceps peak torque; however, there was a significant increase (P < .05) between preseason and prenationals (23.39 N·m). Peak torque at fatigue was greater (P < .05) at midseason than preseason, representing an increase of 9.82 N·m. Between midseason and prenationals testing, we observed an 11% increase (P < .05) in %DCLN. Finally, we noted an increase (P < .05) from 0.6 to 0.69 in peak torque/body mass ratio between preseason and prenationals. Conclusions: Our results indicate that while force values seem to suffer at midseason, the wrestlers compensated and were strongest just before their national competition.